Lectotypifications and nomenclatural notes in the Boraginaceae s.str. for the Flora of Ecuador - Holstein, Norbert; Weigend, Maximilian (Phytotaxa, 2016)
During the preparation of a taxonomic treatment concerning Boraginaceae s.str. for the Flora of Ecuador, we found that there are eleven species currently known in that area. We herewith designate lectotypes for some of the names concerned: Cynoglossum revolutum and Cynoglossum mexicanum (both Hackelia revoluta), Amsinckia hispida and Eritrichium mandonii (both Amsinckia calycina), and Anchusa linifolia and Lithospermum alpinum (both Plagiobothrys linifolius). The complex history of the type material of various synonyms of Plagiobothrys linifolius based on material by Bonpland and Humboldt is briefly discussed.